Subjective well-being and anxiety level during the COVID-2019 crisis: study in Ukrainian adolescence - Maryna Olehivna Orap; Nataliia Volodymyrivna Akimova; Yaroslava Yevhenivna Kalba (Insight: the psychological dimensions of society, 2021)
The global pandemia and introduced quarantine providescompletely new social conditions that affectthe mental health of people. The influence of traitand state anxiety on people with different levels of subjectivewell-being in quarantine remains unexplored. Method: We used the PERMA-Profiler (J. Butler, M.Kern) technique to diagnose the overall level of subjectivewell-being and its components. The STAI method(С. Spielberger) was also used to study the levelof respondent’s trait and state anxiety. Results: It wasfound that the overall level of life satisfaction is significantlynegatively correlated with the level of traitanxiety (r = - .25). The level of state anxiety was unexpectedlylower at the beginning of quarantine (43.95 ±3.90), than one month later (48.50 ± 5.08). Qualitativeanalysis has led to the conclusion that in adolescencethis is due to a lack of awareness of the dangersof a pandemic and the general attitude to quarantineas a holiday and vacation. There was an inverse relationshipbetween anxiety and positive emotions beforethe quarantine, but under quarantine, positive emotionslost their potential to contain anxiety, and correlationswere insignificant, so even positive eventsunder quarantine could not reduce COVID-19 anxiety.However, the general level of subjective well-beingof Ukrainian youth does not correlate with the levelof anxiety and has not changed significantly duringthe first months of the quarantine. Conclusions: Theconcept of subjective well-being of Ukrainian youthis based primarily on subjective indicators of positiveemotions and meanings and much less depends onmore objective criteria, such as health, engagementand accomplishment. It was found that during the firstmonth of the quarantine, the level of state anxiety didnot affect the experience of subjective well-being byUkrainian adolescence.